Cognitive tool: Learning forces for beginners / Kamarul Naemi Kamarudin - Kamarul Naemi, Kamarudin (2004)
Many subjects taught in school are supported by CAI software. Learning about forces is difficult if it is learned theoretically. Students fail to understand the basic concept of forces, therefore they generalize that learning physics is difficult. The purpose of this research is to develop a prototype that can make learning physics fun and easy. The tool guides students to identify and draw forces acting on objects and visualize the motions. Lessons, questions and learning activities are provided, supported with animated examples. Students are guided through problem so as to relate the ideas to be learnt to those acquired earlier. Results show that they learned and understand the concept better.